2012
DOI: 10.1002/elps.201200024
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bioconjugation of quantum dots using capillary electrophoresis and fluorescence correlation spectroscopy

Abstract: In this paper, we systematically investigated the conjugation of quantum dots (QDs) with certain biomolecules using capillary electrophoresis (CE) and fluorescence correlation spectroscopy (FCS) methods. Commercial QDs and aqueous-synthesized QDs in our lab were used as labeling probes, certain bio-macromolecules, such as proteins, antibodies, and enzymes, were used as mode samples, and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysulfo-succinimide (Sulfo-NHS) were used as li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…CE-FL has been shown to be an effective method to detect QDs-protein interaction, which reveals subtle changes in the structure and composition of the surface bound ligands on QDs [21,30]. CE-FL can provide far more detailed information on QDs-protein assembly than ensemble fluorescence measurement [21].…”
Section: Resultsmentioning
confidence: 99%
“…CE-FL has been shown to be an effective method to detect QDs-protein interaction, which reveals subtle changes in the structure and composition of the surface bound ligands on QDs [21,30]. CE-FL can provide far more detailed information on QDs-protein assembly than ensemble fluorescence measurement [21].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that BPP values of QD-TBA were stable before and after the SEC separations, while BPP values were remarkably reduced with the increased ultrafiltration times. According to our previous experiment experiences [62] and the manufacture's suggestion, more than three repeated ultrafiltration operations were required in order to completely remove the unreacted aptamer. Herein, on comparison, SEC was more suitable for the purification of QD-TBA in our case.…”
Section: Purification Strategies Of Qd-tbamentioning
confidence: 99%
“…Then, 1 mL of EDC (at 4 mg.mL -1 ) was added and after 5 min, 1 mL of Sulfo-NHS (at 5.5 mg.mL -1 ) was also added to the QDs aqueous suspension [21,22]. Then, 15 min later, 194 µL of Tf (at 1 mg.mL -1 ) was added to reach a ratio of QDs:Tf 1:2 (particle:molecule).…”
Section: Cdte-msa Qds Conjugation To Transferrinmentioning
confidence: 99%